Schlachtfelder - Langthaler, Ernst (2016)
Taking the province of Niederdonau as an example, this pioneer study highlights everyday fields-of-force between National Socialism and agrarian society in which rural actors competed for resources among themselves and with official functionaries. The megaproject of ‘volkish productivism’ – the creation of an efficient peasantry in ‘racial’ and economic terms – got stuck with regard to technical development. However, with regard to institutional development, there emerged a pathway towards an alternative modernity beyond Liberalism and Communism. Diese Pionierstudie beleuchtet am Beispiel des Reichsgaues Niederdonau alltägliche Kräftefelder zwischen Nationalsozialismus und Agrargesellschaft, in denen ländliche Akteure untereinander und mit Funktionsträgern um Ressourcen rangen. Das Entwicklungsprojekt des ‚völkischen Produktivismus‘ – die Erzeugung eines „rassisch“ und wirtschaftlich leistungsfähigen „Bauerntums“ – blieb zwar in technischer Hinsicht stecken. Jedoch stellte es in institutioneller Hinsicht die Weichen der Agrarentwicklung in Richtung einer alternativen Moderne jenseits von Liberalismus und Kommunismus.